COVID-19 is a persistent reallocation shock - Jose Maria Barrero; Nicholas Bloom; Steven J. Davis; Brent H. Meyer (Federal Reserve Bank of Atlanta, 2021)
Drawing on data from the firm-level Survey of Business Uncertainty, we present three pieces of evidence that COVID-19 is a persistent reallocation shock. First, rates of excess job and sales reallocation over 24-month periods have risen sharply since the pandemic struck, especially for sales. We compute these rates by aggregating over monthly firm-level observations that look back 12 months and ahead 12 months. Second, as of December 2020, firm-level forecasts of sales revenue growth over the next year imply a continuation of recent changes, not a reversal. Third, COVID-19 shifted relative employment growth trends in favor of industries with a high capacity of employees to work from home and against those with a low capacity.
Keywords: D22; D84; E23; E24; J21; J62; J63; 330; COVID-19; reallocation shock; business expectations; working from home; Survey of Business Uncertainty